2003
DOI: 10.1021/jp036715g
|View full text |Cite
|
Sign up to set email alerts
|

Reversibly Altering Electronic Conduction through a Single Molecule by a Chemical Binding Event

Abstract: This letter presents experimental evidence that the electrical conductance of a single molecule can be altered by a chemical binding event. Self-assembled monolayers of electron donor tetramethyl xylyl dithiol (TMXYL) have been synthesized and chemically switched to a conducting state by reaction with an electron acceptor tetracyanoethylene (TCNE). Low bias conductance measurements obtained by scanning tunneling spectroscopy under ultrahigh vacuum conditions show a change from insulating to ohmic behavior as a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
42
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(44 citation statements)
references
References 32 publications
2
42
0
Order By: Relevance
“…Thus, DTs electrochemical desorption can be better understood by making additional considerations, like the way that the DT molecules are bonded to the surface, and the interactions/bonds between DT molecules. Regarding the bonding of DT molecules to the surface, it gives origin to structures where DT molecules can present standing-up (Schemes 1d-j) [4][5][6][7] or lying-flat (Scheme 1k) [7][8][9][10] configuration. For the ideal DT (…”
Section: Background Concepts and Bibliographic Surveymentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, DTs electrochemical desorption can be better understood by making additional considerations, like the way that the DT molecules are bonded to the surface, and the interactions/bonds between DT molecules. Regarding the bonding of DT molecules to the surface, it gives origin to structures where DT molecules can present standing-up (Schemes 1d-j) [4][5][6][7] or lying-flat (Scheme 1k) [7][8][9][10] configuration. For the ideal DT (…”
Section: Background Concepts and Bibliographic Surveymentioning
confidence: 99%
“…In particular, when these molecules have the same affinity to the surface to both ends (e.g. a,x-alkanedithiols), they could be adsorbed in an upright (mono-coordinated) [4][5][6][7] or a lying down configuration (bi-coordinated) [6][7][8][9][10] depending on the preparation method (UHV, solutions, etc.) and the surface coverage.…”
Section: Introductionmentioning
confidence: 99%
“…[5] Alternatively, molecular switches can be operated nonconformationally by redox reactions [6] or a chemical binding event. [7] Biomolecules have recently been adapted for new purposes; for example, DNA has been used as part of a conducting wire, [8] a molecular machine, [9][10][11][12] a crystal template, [13] a scaffold for nanoscale construction, [14] and even as a component of a "computing machine". [15,16] Herein we show that the fluorescence of individual dye-labeled DNA molecules can be reversibly switched from green to red and vice versa upon application of an electric field.…”
mentioning
confidence: 99%
“…In addition to the control of 1,4-phenylenedimethanethiol structures on Au(111) imparted by the deposition conditions, we found that chemical doping also resulted in re-arrangment of the molecules. Using a procedure first reported by Labonte et al [5], addition of a strong electron acceptor (in this case, tetracyanoethylene, TCNE) caused the previously upright molecules to adopt a horizontal configuration with respect to the gold surface, as shown in Figure 3A. Figure 3B shows an STM image of the 1,4-phenylenedimethanethiol molecules on Au(111) in this horizontal arrangement.…”
Section: Resultsmentioning
confidence: 86%